2021
DOI: 10.3906/sag-2012-327
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 associated rhabdomyolysis in 32 patients

Abstract: Background/aim: This mini-review aims at summarising and discussing previous and recent findings concerning the clinical manifestations, therapeutic management, and outcome of SARS-CoV-2 associated rhabdomyolysis. Materials and methods: literature search in the PubMed database applying appropriate search terms. Results: identified were 26 articles reporting SARS-CoV-2 associated rhabdomyolysis in 32 patients. Age ranged from 16 to 80 years. Four patients were female and 25 male. Onset of rhabdomyolysis was pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 5 publications
0
25
0
Order By: Relevance
“…Meta-analytic studies indicate that myalgia (muscle soreness)/fatigue is the third most common symptom (after unremitting fever and cough) in people with symptomatic SARS-CoV-2 infection [8,9]. The duration of myalgia depends primarily on disease severity [12,13]. Imaging data from hospitalized patients in China showed that muscle ache on admission is associated with abnormal images of the lung, and it predicts poor prognosis, especially in older people [14].…”
Section: Overviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Meta-analytic studies indicate that myalgia (muscle soreness)/fatigue is the third most common symptom (after unremitting fever and cough) in people with symptomatic SARS-CoV-2 infection [8,9]. The duration of myalgia depends primarily on disease severity [12,13]. Imaging data from hospitalized patients in China showed that muscle ache on admission is associated with abnormal images of the lung, and it predicts poor prognosis, especially in older people [14].…”
Section: Overviewmentioning
confidence: 99%
“…They also interfere with hormones that promote muscular integrity, such as testosterone [19]. In rare cases, viral-induced myotoxicity was reported [13]. Renal injury noted by macrohematuria or even renal failure is reported along with myalgia in COVID-19 patients with rhabdomyolysis, denoting a possible renal involvement in COVID-19-related muscle damage [13,20].…”
Section: Possible Mechanisms Of Muscle Damage In Covid-19mentioning
confidence: 99%
See 3 more Smart Citations